Multidrug resistant bacteria isolated from septic arthritis in horses - Motta, Rodrigo G. [UNESP]; Martins, Lorrayne S.A.; Motta, Igor G.; Guerra, Simony T. [UNESP]; de Paula, Carolina L. [UNESP]; Bolanos, Carmen Alicia Daza [UNESP]; da Silva, Rodrigo Costa; Ribeiro, Marcio Garcia [UNESP] (FapUNIFESP (SciELO), 2017)
Septic arthritis is a debilitating joint infectious disease of equines that requires early diagnosis and immediate therapeutic intervention to prevent degenerative effects on the articular cartilage, as well as loss of athletic ability and work performance of the animals. Few studies have investigated the etiological complexity of this disease, as well as multidrug resistance of isolates. In this study, 60 horses with arthritis had synovial fluid samples aseptically collected, and tested by microbiological culture and in vitro susceptibility test (disk diffusion) using nine antimicrobials belonging to six different pharmacological groups. Bacteria were isolated in 45 (75.0%) samples, as follows: Streptococcus equi subsp. equi (11=18.3%), Escherichia coli (9=15.0%), Staphylococcus aureus (6=10.0%), Streptococcus equi subsp. zooepidemicus (5=8.3%), Staphylococcus intermedius (2=3.3%), Proteus vulgaris (2=3.3%), Trueperella pyogenes (2=3.3%), Pseudomonas aeruginosa (2=3.3%), Klebsiella pneumoniae (1=1.7%), Rhodococcus equi (1=1.7%), Staphylococcus epidermidis (1=1.7%), Klebsiella oxytoca (1=1.7%), Nocardia asteroides (1=1.7%), and Enterobacter cloacae (1=1.7%). Ceftiofur was the most effective drug (> 70% efficacy) against the pathogens in the disk diffusion test. In contrast, high resistance rate (> 70% resistance) was observed to penicillin (42.2%), enrofloxacin (33.3%), and amikacin (31.2%). Eleven (24.4%) isolates were resistant to three or more different pharmacological groups and were considered multidrug resistant strains. The present study emphasizes the etiological complexity of equine septic arthritis, and highlights the need to institute treatment based on the in vitro susceptibility pattern, due to the multidrug resistance of isolates. According to the available literature, this is the first report in Brazil on the investigation of the etiology. of the septic arthritis in a great number of horses associated with multidrug resistance of the isolates.
Keywords: Antimicrobial resistance; Arthritis; Etiology; Horses; Joint infectious diseases